2008
DOI: 10.1534/genetics.108.092106
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Acp29AB, a Predicted Seminal Fluid Lectin, in Female Sperm Storage inDrosophila melanogaster

Abstract: Females of many animal species store sperm for taxon-specific periods of time, ranging from a few hours to years. Female sperm storage has important reproductive and evolutionary consequences, yet relatively little is known of its molecular basis. Here, we report the isolation of a loss-of-function mutation of the Drosophila melanogaster Acp29AB gene, which encodes a seminal fluid protein that is transferred from males to females during mating. Using this mutant, we show that Acp29AB is required for the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
91
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 70 publications
1
91
0
Order By: Relevance
“…Sperm storage contains multiple steps that ensure the efficiency of the process, with these steps regulated by several seminal proteins (Acps) received by the female during mating (17)(18)(19)(20)(21). The Acps we studied here are influential in at least two ways: (1) by affecting the number of sperm that get stored (Acp36DE) and (2) by affecting the number of sperm that are retained within the SSOs (19), which could underlie their effects on males' success in sperm competition situations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperm storage contains multiple steps that ensure the efficiency of the process, with these steps regulated by several seminal proteins (Acps) received by the female during mating (17)(18)(19)(20)(21). The Acps we studied here are influential in at least two ways: (1) by affecting the number of sperm that get stored (Acp36DE) and (2) by affecting the number of sperm that are retained within the SSOs (19), which could underlie their effects on males' success in sperm competition situations.…”
Section: Resultsmentioning
confidence: 99%
“…The process of sperm storage involves several different steps: the entry of sperm into storage, their retention and maintenance in storage, and their release from storage (1). In D. melanogaster, Acps have been shown to be necessary for sperm storage, and individual steps of the process appear to be controlled separately by different Acps (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Previous work in Drosophila has demonstrated that male genotype (Clark et al 1995(Clark et al , 1999Fiumera et al 2005Fiumera et al , 2007Civetta et al 2008;Chow et al 2010), female genotype (Clark et al 1995(Clark et al , 1999Clark and Begun 1998;Civetta et al 2008;Chow et al 2010) male · female genotype interactions (Clark and Begun 1998;Clark et al 1999;Chow et al 2010) are all important to the outcome of sperm competition and that each aspect involves dozens of genes. Functional and association studies demonstrated that several male-derived accessory gland proteins (Acps) play important roles in sperm competition (Harshman and Prout 1994;Fiumera et al 2005Fiumera et al , 2007Wong et al 2008;Avila and Wolfner 2009;Chow et al 2010). However, while different female genotypes associate with differences in sperm competition outcomes, little is known about the specific genes or gene variants that underlie the differences in the female side of sperm competition.…”
mentioning
confidence: 99%
“…Functional and association studies demonstrated that several male-derived accessory gland proteins (Acps) play important roles in sperm competition (Harshman and Prout 1994;Fiumera et al 2005Fiumera et al , 2007Wong et al 2008;Avila and Wolfner 2009;Chow et al 2010). However, while different female genotypes associate with differences in sperm competition outcomes, little is known about the specific genes or gene variants that underlie the differences in the female side of sperm competition.…”
mentioning
confidence: 99%
“…These changes are mediated by Acp36DE, an SFP required for efficient accumulation of sperm into storage (Neubaum and Wolfner 1999;Bloch Qazi and Wolfner 2003;Avila and Wolfner 2009). Upon entry into storage, sperm are maintained in the storage organs before they are released for utilization; both of these mechanisms are influenced by SFPs (Ravi Ram and Wolfner 2007a;Wong et al 2008). Here, we determined the role of SP in sperm dynamics by examining uterine conformation, total sperm storage, sperm release, and sperm competition in the presence or absence of SP in the male ejaculate.…”
mentioning
confidence: 99%